Evaluation of Caesalpinia bonduc seed coat extract for anti-inflammatory and analgesic activity - Dayanand M Kannur; Mukta P Paranjpe; Lalit V Sonavane; Prerana P Dongre; Kishanchand R Khandelwal (Wolters Kluwer Medknow Publications, 2012)
In the present work, Caesalpinia bonduc seed coat extract (CBSCE) has been evaluated for anti-inflammatory and analgesic activity C. bonduc seeds have been attributed with anti-inflammatory and analgesic properties in the folklore medicine. Here in our study, we have tried to carry out the systematic evaluation of the seed coat extract of C. bonduc to substantiate these claims. C. bonduc seed coat was extracted with 95% ethanol and concentrated; further, the extract was screened for anti-inflammatory and analgesic activity. The studies were carried using Carrageenan-induced Paw Edema, Egg albumin-induced paw edema, Eddy's Hot Plate Test, Tail Immersion Method so as to prove acclaimed properties. The data was analyzed statistically by Students' 't' test. The results indicate that seed coat extract has the ability to decrease the induced inflammation at varied doses in Carrageenan model as well as in the Egg albumin model in rats. The antinociceptive results indicate that the extract has the ability to increase the pain threshold of the animals and reduce the pain factor, thereby inducing analgesia. Thus, it can be concluded that CBSCE posses analgesic and anti-inflammatory activity.